Investigation of chessboard scanning strategy in selective laser melting of ti6al4v - Amirah Salsabila Widad Putri; Sugeng Supriadi; Bambang Suharno (Prosiding SNTTM, 2025)
Selective Laser Melting (SLM) is recognized as a technology capable of producing metallic components with advantages in geometric flexibility and consistency of mechanical properties. mong the various alloys processed through SLM, titanium alloy Ti6Al4V is particularly attractive due to its superior strength-to-weight ratio, corrosion resistance, and thermal stability. Nevertheless, the quality of as-SLM Ti6Al4V parts is strongly affected by the selection of process parameters. In particular, the laser scanning strategy plays a decisive role in governing energy distribution, thermal gradients, and subsequent microstructural evolution during fabrication. One of the scanning approaches, the chessboard strategy, has gained significant attention because it subdivides the building area into smaller islands that are scanned alternately, reducing scan length and promoting more uniform heat distribution. This study investigates the application of the chessboard strategy in fabricating cylindrical Ti6Al4V specimens, with process maintained constantly. The fabricated geometry exhibited good agreement with the original design, confirming the capability of SLM to reproduce complex features under controlled conditions. Surface characterization revealed protrusions on the top surface (upskin), attributed to excess energy accumulation at the end of scan tracks, while fine wavy-bulgy patterns were observed on the lateral surfaces due to overlapping melt pools and re-solidified particles. The measured average surface roughness (Ra) was 4.275 ± 0.655 µm, falling within an acceptable range for SLM-fabricated components. In addition, scanning electron microscopy (SEM) analysis revealed the presence of lack-of-fusion porosity, indicating localized imperfections in powder melting and consolidation. Overall, the findings highlight that the chessboard scanning strategy not only influences thermal distribution but also directly affects surface morphology and porosity characteristics, providing essential insights for optimizing as-SLM Ti6Al4V.